2016
DOI: 10.1242/dmm.025452
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model for ulcerative colitis based on NOD-scid IL2R γnull mice reconstituted with peripheral blood mononuclear cells from affected individuals

Abstract: Animal models reflective of ulcerative colitis (UC) remain a major challenge, and yet are crucial to understand mechanisms underlying the onset of disease and inflammatory characteristics of relapses and remission. Mouse models in which colitis-like symptoms are induced through challenge with toxins such as oxazolone, dextran sodium sulfate (DSS) or 2,4,6-trinitrobenzenesulfonic acid (TNBS) have been instrumental in understanding the inflammatory processes of UC. However, these neither reflect the heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
7
26
0
Order By: Relevance
“…The current study also demonstrates that humanized NSG mice engraft human monocytes and DCs. Previous studies have shown that NSG mice engraft human monocytes and DCs when injected with human cord blood, and engraft human monocytes when injected with hPBMCs . Similarly, SCID mice injected with hPBMCs engraft human DCs, but the current study is the first to demonstrate DC engraftment in NSG mice injected with hPBMCs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The current study also demonstrates that humanized NSG mice engraft human monocytes and DCs. Previous studies have shown that NSG mice engraft human monocytes and DCs when injected with human cord blood, and engraft human monocytes when injected with hPBMCs . Similarly, SCID mice injected with hPBMCs engraft human DCs, but the current study is the first to demonstrate DC engraftment in NSG mice injected with hPBMCs.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have shown that NSG mice engraft human monocytes and DCs when injected with human cord blood, 38 and engraft human monocytes when injected with hPBMCs. 39,40 Similarly, SCID mice injected with hPBMCs engraft human DCs, 41 but the current study is the first to demonstrate DC engraftment in NSG mice injected with hPBMCs. Human T cells recognize murine major histocompatibility complex I and II molecules in NSG mice to cause GVHD, 27 but the identity of the APCs involved remains to be determined.…”
Section: Discussionmentioning
confidence: 69%
“…To examine the role of autoantigens in an inflammatory environment in vivo, the effect of CD99 was analyzed in NSG-UC model [7,9,23]. NSG mice were reconstituted with PBMC from donors with UC and additionally challenged with CD99.…”
Section: Additional Challenge With Cd99 Aggravates Disease Symptoms Amentioning
confidence: 99%
“…In order to gain a better understanding of the inflammatory processes an animal model was developed which is based on NOD-scid IL2Rγ null (NSG) mice reconstituted with PBMC from diseased UC-individuals (NSG-UC model) [7,8]. Challenge of mice with ethanol evoked symptoms and phenotype similar to the human disease and treatment with infliximab promoted a remodeling condition characterized by increased fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preclinical models with better reflection of human disease are needed. Recently, a humanized mouse model that mimics disease patterns of patients with UC has been successfully established [50]. Peripheral blood mononuclear cells of stratified patients with UC are injected in immunodeficient NOD/scid IL2R-γnull mice.…”
Section: New Therapeutic Approachesmentioning
confidence: 99%